1993
DOI: 10.1034/j.1600-0889.1993.t01-2-00001.x
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric deposition to a high-elevation forest at Whiteface Mountain, New York, USA

Abstract: Atmospheric deposition rates have proven difficult to quantify in mountainous settings but must be estimated in order to assess the potential impact of air pollution on high‐elevation ecosystem processes. We measured major ion concentrations in precipitation, cloud water and aerosols as well as the concentrations of the pollutant gases SO2 and HNO3 vapor in a subalpine spruce‐fir forest at Whiteface Mountain, New York, USA, for a 4‐yr period beginning in June of 1986. Deposition of S, N and major elements to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
3

Year Published

1993
1993
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 0 publications
2
28
3
Order By: Relevance
“…However, the rate of S deposition via fog, wet and dry deposition in high-elevation forests in the US (16.3 kg S ha −1 yr −1 ) (Miller et al, 1993) and Japan (16.7-27.7 kg S ha −1 yr −1 ) (Shimadera et al, 2012) was also significantly lower than that of the present study. Future estimates from CMAQ simulations indicate that northcentral and eastern China are expected to receive the highest S depositions resulting from a high density of energy consumption and emissions (Zhao et al, 2009).…”
Section: Spatio-temporal Variations Of T So X In Northern Chinacontrasting
confidence: 55%
See 1 more Smart Citation
“…However, the rate of S deposition via fog, wet and dry deposition in high-elevation forests in the US (16.3 kg S ha −1 yr −1 ) (Miller et al, 1993) and Japan (16.7-27.7 kg S ha −1 yr −1 ) (Shimadera et al, 2012) was also significantly lower than that of the present study. Future estimates from CMAQ simulations indicate that northcentral and eastern China are expected to receive the highest S depositions resulting from a high density of energy consumption and emissions (Zhao et al, 2009).…”
Section: Spatio-temporal Variations Of T So X In Northern Chinacontrasting
confidence: 55%
“…5), which fall within the range of 1.9-13 keq ha −1 yr −1 in the forested catchments in Southern China (Larssen et al, 2011). However, the acid deposition in the study is approximately 10 times the results in Malaysia (0.3-0.5 keq ha −1 yr −1 ) (Ayers et al, 2000) and is also much higher than the earlier estimates from highelevation forests in the US (2.2 keq ha −1 yr −1 ) (Miller et al, 1993) and the values (0.8-1.9 keq ha −1 yr −1 ) reported by CASTNET, EMEP and EANET (Endo et al, 2010). The level of acid deposition in Northern China is sufficiently high to suggest the need for an integrated assessment of the acidic deposition and its potential environmental consequences for the region (Hao et al, 2001;Larssen et al, 2011;Yang et al, 2012b;Zhao et al, 2009).…”
Section: Acid Deposition In Northern China and Its Implicationscontrasting
confidence: 50%
“…This allows for comparisons with other studies, which are shown in 21 Miller et al, 43 Miller et al, 44 and Lindberg. 45 Table 5 For the site at Mt.…”
Section: Cloud Water Chemistrymentioning
confidence: 90%
“…Therefore, cloud water ion concentrations have been estimated at lower elevations by converting the summit cloud chemistry observations to air concentrations and calculating the ion concentrations at the elevation of interest using the estimated LWC and a constant scavenging efficiency. 44 • Cloud immersion frequency is also strongly dependent on elevation in the northeastern United States. Miller et al 43 reported an exponential increase in immersion frequency with elevation at Whiteface Mountain.…”
Section: Model Sensitivitymentioning
confidence: 99%
“…Such an approach is supported by the fact that many observational studies indicate that the mode or mean diameter of fog droplets correlates with LWC [e.g., Joslin et al ., ]. This approach was also used in later modeling studies [ Miller et al ., , ; Katata et al ., ]. Vong et al .…”
Section: Fogwater Deposition Modelingmentioning
confidence: 99%